The unsustainability of occupational based model diagrams. (2nd October 2020) - Reid, Heleen A. J.; Hocking, Clare; Smythe, Liz
Abstract: Background: Occupation-based models are generic explanations of occupational engagement. Their associated diagrams are conceptual tools that represent the key concepts and their interrelationships, which have withstood substantial shifts in the profession's knowledge base and scope over the last 30–40 years. Aims: We aim to bring into question the sustainability of the diagrams used to represent models. Methods: Intellectual history and semiotic analysis are combined as tools for examining the history of selected occupation-based models and the convention of representing them diagrammatically. Our critique employs a hermeneutically inspired semiotic technique to scrutinise the diagrams as stand-alone symbolic objects. Results: We argue that the rigid categorisation and oversimplified structure of diagrams keeps the profession pinned to dated perspectives based in positivism and dualism, bypassing the real, lived experiences of people. Our critique highlights the ontological absences from diagrammatic representations of occupation-based models. Conclusions: The continued practice of depicting models with diagrams needs to change, to create space to integrate other theory and perspectives, such as a more fundamentally human, ontological perspective. Significance: An ontological perspective is important for practice to advance past the dualistic or pluralistic stance the profession has held for decade, to understand how people experience their world rather than how the profession sees a person's world.